Tourist experiences shared and viralized by travelers through networks: factors and facilitators - Sacaluga Rodríguez, Ignacio; Vargas Delgado, José Jesús; Pérez García, Álvaro (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The objectives of our study will be based on delving into the fact that the true prosumer has shaped the personification of absolute interactivity in the generation of messages, stories or any other type of content. Therefore, it is emphasized that not only its structure and its ingredients are transcendental for the effectiveness of a narrative, but also the way in which it is told, the medium used and the viewing platform. The sense of the fragmentation of the narrative itself is also relevant for the success of its argumentative and emotional hyperconnectivity.